RELATIONSHIP BETWEEN FOODING BEHAVIOR BY MOTHER WITH NUTRITIONAL STATUS OF TODDLERS IN ARONGAN VILLAGE, NAGAN RAYA REGENCY - Eliyana Eliyana; Enda Silvia Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
In Indonesia, the problem of nutrition is still very high, we should prepare the Indonesian generation in a healthy, intelligent and quality manner to be able to continue the development of the Indonesian nation to be more advanced, just and prosperous. The survey results obtained data for 72 children under five, there were 83.3% under five with good nutritional status, 2.8% under five with overweight status, 12.5% ​​under five with malnutrition status, and 1.4% under five with poor nutritional status. The purpose of the study was to determine the relationship between knowledge, attitudes and actions of mothers in giving food to the nutritional status of children under five. This study used a cross sectional analytic survey, the primary data was obtained from the measurement of the toddler's weight. The population of this research is all mothers who have toddlers totaling 72 respondents, the sample in this study is all of the total population. The research analysis was univariate and bivariate using the Chi-Square test. The results showed that there was a relationship between mother's knowledge (P-value = 0.001), mother's attitude (P-value = 0.02), and mother's actions (P-value = 0.01) with the nutritional status of children under five.